Transparency during public health emergencies: from rhetoric to reality - P O'Malley; J Rainford; A Thompson (The World Health Organization, 2009)
Effective management of public health emergencies demands open and transparent public communication. The rationale for transparency has public health, strategic and ethical dimensions. Despite this, government authorities often fail to demonstrate transparency. A key step in bridging the gap between the rhetoric and reality is to define and codify transparency to put in place practical mechanisms to encourage open public health communication for emergencies. The authors demonstrate this approach using the example of the development and implementation process of a public health emergency information policy.